JENIS-JENIS KAPANG PENGONTAMINASI CABE GILING DARI BEBERAPA PASAR TRADISIOANAL DI KOTA PADANG - Subandini, Nani; Fifendy, Mades; Periadnadi, Periadnadi (STKIP PGRI Sumbar, 2013)
ABSTRACT Ground cayenne pepper is one of the preparations that are sold in the markets. Cayenne is one food that is often contaminated by soil, dirt and microorganisms. Contamination can occur during harvesting, transport, processing and marketing. The purpose of this study to determine the types of molds contaminating ground pepper. This study uses purposive sampling method with mold growing on Potato Dextrose Agar media and create later identify pure culture. Results of this study are 5 types of molds are milled pepper pengkontaminsi Aspergillus ustus, Aspergillus niger, Aspergillus sp, Rhizopus stolonifer and Penicillium corylophilum.